The The Analysis Of Technological Pedagogical And Content Knowledge (Tpack) Economics Teachers - Neti Budiwati; Suparno; Kodri Kodri (Jurnal Ilmiah Econosains, 2019)
The aim of this study was to describe the Technological Pendagogical and Content Knowledge (TPACK) economics teacher of high schools in Lampung Province. The method used in this research is descriptive method with data collection techniques through distributing questionnaires to economics teachers. The questionnaire consisted of 31 items and 7 subdomains. The seven subdomains are Technological Knowledge (TK), Pendagogical Knowledge (PK), Content Knowledge (CK), Technological Pendagogical Knowledge (TPK), Technological Content Knowledge (TCK), Pendagogical Content Knowledge (PCK) and Technological Pendagogical Content Knowledge (TPCK) . The subjects of this study were 33 teachers chosen at random. Data analysis techniques using descriptive analysis. The results showed that kindergarten teachers of economics at Public High Schools in Lampung Province included in the moderate category (M = 5.37), moderate PK (M = 5.62), moderate CK (M = 5.43), moderate TPK (M = 5.65), moderate TCK (M = 5.66), moderate PCK (M = 5.69) and good TPCK (M = 5.42). The overall economic teacher TPCK is moderate (M = 5.54). The results show that economics teachers at SMA Negeri Sekolah in Lampung Province can apply their technological knowledge in economic learning.